2019
DOI: 10.2106/jbjs.19.00817
|View full text |Cite
|
Sign up to set email alerts
|

A Primer on Clinically Important Outcome Values

Abstract: ➤ Clinically important outcome values allow physicians to provide patients with more realistic expectations regarding their treatment that are based on their specific demographics.➤ Clinically important outcome values can vary for the same procedure or population depending on the method of calculation used, which raises the need for uniform ways to calculate and compare these values across populations and procedures.➤ A shift in approach from focusing solely on significant outcomes, or p values, to considering… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 40 publications
0
22
0
Order By: Relevance
“…22 Group-level differences between PROM scores do not guarantee a perceptible or clinically meaningful difference for individual patients. [7][8][9] As an alternative, CIOVs translate PROM scores into clinically relevant terms and therefore may provide better benchmarks for individual patient success. [7][8][9] Bodendorfer et al 4 reported PASS scores for the question ''Do you consider that your current state is satisfactory?''…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 Group-level differences between PROM scores do not guarantee a perceptible or clinically meaningful difference for individual patients. [7][8][9] As an alternative, CIOVs translate PROM scores into clinically relevant terms and therefore may provide better benchmarks for individual patient success. [7][8][9] Bodendorfer et al 4 reported PASS scores for the question ''Do you consider that your current state is satisfactory?''…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] As an alternative, CIOVs translate PROM scores into clinically relevant terms and therefore may provide better benchmarks for individual patient success. [7][8][9] Bodendorfer et al 4 reported PASS scores for the question ''Do you consider that your current state is satisfactory?'' in patients at 1 year after hip arthroscopy for FAIS.…”
Section: Discussionmentioning
confidence: 99%
“…This score is derived from 5 items, each having five response options. To determine the PASS of the MHQ pain score, we asked patients to answer the following anchor question [ 23 ]: “How satisfied are you with your treatment results thus far?” with response options: “excellent,” “good,” “fair,” “moderate,” or “poor.” Considering that the PASS represents the threshold above which a patient is satisfied with his or her current state [ 3 ], we adopted the threshold between “fair” and “good” as the PASS and dichotomized the ratings accordingly.…”
Section: Methodsmentioning
confidence: 99%
“…with response options: "excellent," "good," "fair," "moderate," or "poor." Considering that the PASS represents the threshold above which a patient is satisfied with his or her current state [3], we adopted the threshold between "fair" and "good" as the PASS and dichotomized the ratings accordingly.…”
Section: Real Dataset: Patient Acceptable Symptom State (Pass)mentioning
confidence: 99%
See 1 more Smart Citation